2021
DOI: 10.1038/s41396-021-00899-w
|View full text |Cite
|
Sign up to set email alerts
|

Experimental identification and in silico prediction of bacterivory in green algae

Abstract: While algal phago-mixotrophs play a major role in aquatic microbial food webs, their diversity remains poorly understood. Recent studies have indicated several species of prasinophytes, early diverging green algae, to be able to consume bacteria for nutrition. To further explore the occurrence of phago-mixotrophy in green algae, we conducted feeding experiments with live fluorescently labeled bacteria stained with CellTracker Green CMFDA, heat-killed bacteria stained with 5-(4,6-dichlorotriazin-2-yl) aminofluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 87 publications
(119 reference statements)
2
33
0
Order By: Relevance
“…We predict the trophic modes of B. bigelowii and a mixotrophic haptophyte Haptolina brevifila using the transcriptomes, based on the methods by Burns et al (2018) and Bock et al (2021) . In this model-based analysis, the probability of potential phagocytosis of organisms is evaluated with the scores of 0 to 1.…”
Section: Methodsmentioning
confidence: 99%
“…We predict the trophic modes of B. bigelowii and a mixotrophic haptophyte Haptolina brevifila using the transcriptomes, based on the methods by Burns et al (2018) and Bock et al (2021) . In this model-based analysis, the probability of potential phagocytosis of organisms is evaluated with the scores of 0 to 1.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies revealed the possibility of bacterivory activity of H. akashiwo (31)(32)(33), while the ecophysiological feature of the species has been rarely discussed in depth since then. A recent study predicted the bacterivory potentials of several green algae based on their gene sets and confirmed the activity experimentally (45),suggesting that the usage of both photosynthesis and phagocytosis for survival may be more common than previously considered. Phagocytotic and photosynthetic capabilities of the organisms were computationally predicted using the predictTrophicMode tool using default mode (38,45).…”
Section: Resultsmentioning
confidence: 60%
“…A recent study predicted the bacterivory potentials of several green algae based on their gene sets and confirmed the activity experimentally (45),suggesting that the usage of both photosynthesis and phagocytosis for survival may be more common than previously considered. Phagocytotic and photosynthetic capabilities of the organisms were computationally predicted using the predictTrophicMode tool using default mode (38,45). We analyzed the gene models predicted based on the transcriptomes of various algal species presented in Table 3 and ourH.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…However, from the late spring onwards, freshwater from river runoff and ice melt enforce vertical stratification of the Arctic Ocean, keeping inorganic nutrients below the photic zone. Low nutrient conditions favour smaller species with high surface-to-volume ratios and photo-mixotrophic life strategies (Bock et al, 2021; Jeong et al, 2021; Lie et al, 2018; McKie-Krisberg & Sanders, 2014). Ice-dwelling species are also exposed to salinity fluctuations, nutrient pulses and depletion, and have the ability to maintain viable cells during ice-free periods.…”
Section: Introductionmentioning
confidence: 99%